DENGUE FEVER OUTBREAK IN TWIN CITIES; A TERTIARY CARE CENTER EXPERIENCE: Recent dengue fever outbreak - Khan, Taimoor Ashraf; Nisar, Shazia; Qureshi, Muhammad Mahad; Samiullah, Muhammad; Israr, Muhammad (Pakistan Armed Forces Medical Journal, 2021)
Objective: To characterize the clinical presentations and laboratory markers (as disease predictors and markers) and severity of disease in patients admitted with dengue fever.Study Design: Prospective observational study.Place and Duration of Study: Department of Infectious Diseases, Pak Emirates Military Hospital Rawalpindi, from May to Oct 2018Methodology: In our study, we included the patients treated for dengue fever. Data were recorded on predesigned proforma and analyzed using Microsoft excel 365 and Social Package for Statistical Sciences version 23.Results: A total of 160 patients were included in this study, all were males. All cases were positive for Nonstructural Protein 1 Antigen. Symptoms seen in abundance were fever with rigors, chills, backache, retro-orbital pain, nausea and vomiting. Manual platelet count at admission ranged from 15-396 x 103 (mean 107.5 ± 6.8 x 103). Platelet count on discharge ranged from 102-577 x 103 (mean 207.9 ± 95.4 x 103). A total of 34 (21.25%) patients out of 160 confirmed and admitted dengue fever cases had Dengue Hemorrhagic Fever (Nonstructural Protein 1 Antigen positive, thrombocytopenia and leukopenia) and 2 patient went into dengue shock syndrome. The derangement in alanine aminotransferase and alkaline phosphatase levels were shown in 98 (61.2%) and 62 (31.2%) of patients. All these patients were immunoglobulin M and Nonstructural Protein 1Antigen positive.Conclusion: Raised serum alanine aminotransferase and alkaline phosphatase levels along with early positive Nonstructural Protein 1 Antigen is a marker of disease severity.